The impact of hepatic steatosis on portal hypertension. - Georg Semmler; Bernhard Scheiner; Philipp Schwabl; Theresa Bucsics; Rafael Paternostro; David Chromy; Albert Friedrich Stättermayer; Michael Trauner; Mattias Mandorfer; Arnulf Ferlitsch; Thomas Reiberger (PLoS ONE, 2019)
Background and aims Studies in animal models have suggested that hepatic steatosis impacts on portal pressure, potentially by inducing liver sinusoidal endothelial dysfunction and thereby increasing intrahepatic resistance. Thus, we aimed to evaluate the impact of hepatic steatosis on hepatic venous pressure gradient (HVPG) in patients with chronic liver disease. Method 261 patients undergoing simultaneous HVPG measurements and controlled attenuation parameter (CAP)-based steatosis assessment were included in this retrospective study. Results The majority of patients had cirrhosis (n = 205; 78.5%) and n = 191 (73.2%) had clinically significant portal hypertension (CSPH; HVPG≥10mmHg). Hepatic steatosis (S1/2/3; CAP ≥248dB/m) was present in n = 102 (39.1%). Overall, HVPG was comparable between patients with vs. without hepatic steatosis (15.5±7.5 vs. 14.8±7.7mmHg; p = 0.465). Neither in patients with HVPG (<6mmHg; p = 0.371) nor in patients with mild portal hypertension (HVPG 6-9mmHg; p = 0.716) or CSPH (HVPG≥10mmHg; p = 0.311) any correlation between CAP and HVPG was found. Interestingly, in patients with liver fibrosis F2/3, there was a negative correlation between CAP and HVPG (Pearson's ρ:-0.522; p≤0.001). In multivariate analysis, higher CAP was an independent 'protective' factor for the presence of CSPH (odds ratio [OR] per 10dB/m: 0.92, 95% confidence interval [CI]:0.85-1.00; p = 0.045), while liver stiffness was associated with the presence of CSPH (OR per kPa: 1.26, 95%CI: 1.17-1.36; p≤0.001). In 78 patients, in whom liver biopsy was performed, HVPG was neither correlated with percentage of histological steatosis (p = 0.714) nor with histological steatosis grade (p = 0.957). Conclusion Hepatic steatosis, as assessed by CAP and liver histology, did not impact on HVPG in our cohort comprising a high proportion of patients with advanced chronic liver disease. However, high CAP values (i.e. pronounced hepatic steatosis) might lead to overestimation of liver fibrosis by 'artificially' increasing transient elastography-based liver stiffness measurements.